Age under 20 years, pre‐operative participation in pivoting sports, and steep posterior tibial slope of more than 12° are risk factors for graft failure after double‐bundle anterior cruciate ligament reconstruction - Kazumi Goto; Eisaburo Honda; Hiroshi Iwaso; Shin Sameshima; Miyu Inagawa; Yutaro Ishida; Koji Matsuo; Ryota Kuzuhara; Takaki Sanada (Journal of Experimental Orthopaedics)
Abstract Purpose Younger age and steep posterior tibial slope (PTS) have been reported as risk factors for graft failure after anterior cruciate ligament reconstruction (ACLR). Few studies have evaluated these risk factors simultaneously in a large cohort of patients undergoing double‐bundle ACLR (DB‐ACLR). Therefore, this retrospective study aimed to simultaneously investigate known risk factors such as PTS and age in DB‐ACLR, determine their thresholds and calculate odds ratios (ORs). Methods We investigated 482 knees that underwent DB‐ACLR with a follow‐up period of at least 2 years. Receiver operating characteristic analysis determined cut‐off values for age and PTS for graft failure. Subsequently, logistic regression analysis was conducted to evaluate the effects of age, sex, height, weight, laterality, surgical waiting period, pre‐operative sport type and level, meniscal injury, hyperextension, general joint laxity and PTS on graft failure. Results Graft failure was observed in 33 out of 482 knees (6.8%). Notably, the graft failure group was significantly younger (18.0 ± 5.0 years [standard deviation] vs. 30.4 ± 13.1 years, p < 0.01) and had a steeper PTS (11.9 ± 2.3° [standard deviation] vs. 9.6 ± 2.9°, p < 0.01) than the group with no graft failure. The cut‐off values were 20.0 years for age (specificity, 64.6%; sensitivity, 87.9% and area under the curve, 0.808) and 12.0° for PTS (specificity, 70.9%; sensitivity, 69.7% and area under the curve, 0.734). Logistic regression analysis identified an age of <20 years (OR = 10.1; p < 0.01), PTS of ≥12° (OR = 5.6; p < 0.01) and pre‐operative participation in pivoting sports (OR = 6.0; p < 0.01) as significant risk factors for graft failure. Conclusion We identified an age of <20 years, PTS of ≥12° and pre‐operative participation in pivoting sports as significant risk factors for graft failure after DB‐ACLR. Level of Evidence Level III.